Mixed plant operations for phytoremediation in polluted environments – A critical review - Samudro, Ganjar; Mangkoedihardjo, Sarwoko (Journal of Phytology, 2020)
In this article, a theoretical approach is focusing on the use of mixed plants to remediate polluted environmental media. Essential conditions should be performed, particularly in supporting plant growth, the safety factor for consumers and the use of amendments in improving the efficiency of phytoremediation. In general, it takes more than one type of the plant to be more effective in restoring a polluted environment. For this purpose, the selected plant species mus synergistically eliminate the types of pollutants present in the environmental media. Thus, the mixed plants process becomes very effective in removing many of the pollutants on site. In practice, mixed plants operations could be selected from one or a combination of simultaneous, sequential or alternating patterns, all of which must be adapted to polluted media conditions.